2018
DOI: 10.37358/rc.18.5.6261
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Study of the Interaction of Anticancer Drug Mitoxantrone with Sodium Cholate Aggregates

Abstract: The focus of the present work is to investigate the interaction of anticancer drug mitoxantrone with sodium cholate (NaC) bile salt in phosphate buffer (pH 7.4) and carbonate buffer (pH 10) by UV-Visible absorption spectroscopy. The results indicate that mitoxantrone may bind to NaC monomers and micelles through electrostatic and hydrophobic interactions and the interaction with NaC induces the dissociation of dimers and higher aggregates of mitoxantrone. The stoichiometric ratio, binding constant, micelle/wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The binding constants for the quinizarin interaction with both bile salts micelles are much smaller than the binding constant for the interaction of quinizarin with SDS micelles (2524 M -1 ), 35 probable due to the very different structures between SDS and bile salts micelles. Comparing the value of the binding constant for the interaction of quinizarin with NaC micelles with that for the interaction of mitoxantrone with NaC micelles (4360 M -1 ), 27 we observe that the interaction of mitoxantrone with NaC micelles is stronger than the interaction of quinizarin with NaC micelles. At pH 7.4, mitoxantrone has two positive charges while quinizarin is uncharged, therefore in the case of mitoxantrone the electrostatic interactions between positive charges of mitoxantrone and anionic NaC micelles in addition to hydrophobic interactions can explain the stronger interaction between mitoxantrone and NaC micelles.…”
Section: Determination Of Binding Constant (K B ) and Partition Coefficient (K X )mentioning
confidence: 83%
See 1 more Smart Citation
“…The binding constants for the quinizarin interaction with both bile salts micelles are much smaller than the binding constant for the interaction of quinizarin with SDS micelles (2524 M -1 ), 35 probable due to the very different structures between SDS and bile salts micelles. Comparing the value of the binding constant for the interaction of quinizarin with NaC micelles with that for the interaction of mitoxantrone with NaC micelles (4360 M -1 ), 27 we observe that the interaction of mitoxantrone with NaC micelles is stronger than the interaction of quinizarin with NaC micelles. At pH 7.4, mitoxantrone has two positive charges while quinizarin is uncharged, therefore in the case of mitoxantrone the electrostatic interactions between positive charges of mitoxantrone and anionic NaC micelles in addition to hydrophobic interactions can explain the stronger interaction between mitoxantrone and NaC micelles.…”
Section: Determination Of Binding Constant (K B ) and Partition Coefficient (K X )mentioning
confidence: 83%
“…Micelles of bile salts play an important role in drug delivery and their solubilization process. [24][25][26][27] Bile salts have a very different structure in comparison with conventional surfactants. Bile salts present a large, rigid and planar hydrophobic steroid moiety with attached two or three hydroxyl groups and an anionic carboxyl head group.…”
Section: Introduction *mentioning
confidence: 99%
“…reported that the shape of the MTX absorption spectrum is dependent on its concentration as a consequence of the formation of molecular aggregates in solution [40]; the band at 660 nm was assigned to the monomer and the band at 610 nm to the dimer of MTX. Such a role for the possible dimerization of MTX in concentrated solutions is confirmed by the evidence that at very low concentrations (up to 10 µM) the intensity of both absorption maxima is comparable (see also Fig.…”
Section: Absorption Spectramentioning
confidence: 99%
“…Previously we examined the equilibrium interactions of mitoxantrone with micelles made from different synthetic (sodium dodecyl sulfate (SDS), cetyltrimetylammonium bromide (CTAB), Triton X-100, Brij-35, Tween-20, Tween-80) [39][40][41][42] and natural (sodium taurocholate (NaTC) and sodium taurodeoxycholate (NaTDC) bile salts) surfactants [36] in order to assess the strength of the interaction and the importance of electrostatic and hydrophobic contribution to the drug binding.…”
mentioning
confidence: 99%